P49 Cyproheptadine as an appetite stimulant in the treatment in feeding disorders. (18th November 2019) - Cogings, N; Bryant-Waugh, R; Wong, I; Ooi, K; Hudson, LD
Abstract : Background: Cyproheptadine is an antihistamine with appetite stimulant side-effects. Our service has used Cyproheptadine for feeding disorders in a limited number of patients since 2013 when effects of first line psychological intervention had been limited. Indications were persistent underweight and failure to tube wean. Here we present carer feedback and growth data from with its use. Methods: Retrospective data from all children using Cyproheptadine from 2013-2017 as part of a registered service assessment. Parents completed online questionnaires on their perceived benefits and difficulties using cyproheptadine. Growth data at time from initiation and 6 months reviews was retrieved from patient charts for underweight children. Results: 10 children were prescribed Cyproheptadine, 8 for underweight and 2 to support gastrostomy tube weaning. 2 patients ceased the medication soon after starting (1 due to side effect; 1 due to parental perceived poor efficacy). 9 parents (90%) completed the patient satisfaction survey. There were no serious side adverse effects reported. 8 (88%) of parents said it improved interest in food, and 8 (88%) in amount eaten. Of the 6 children using Cyprohepatdine for underweight both weight z-score and BMI z-score had increased at 6 month follow-up compared to baseline (weight z-score median -2.9 to -2.5 (p=0.03); BMI z-score -3.4 to -2.5 (p =0.04)) Conclusions: From our small number of patient data, Cyproheptadine appears to be safe, effectively improves appetite and quantity eaten by a majority of parents; and also appears to have a positive impact on weight gain in feeding disorders. Further study of its use in this group is needed.